Isolation of piperine from black pepper (Piper nigrum) in the provision of standard compounds for natural chemical practice and research activities - Lalu Sulman (Jurnal Pijar Mipa, 2021)
Research conducted to meet the needs of standard compounds in practical and research activities. The use of standard compounds improves the quality of a study. Piperine is the main secondary metabolite compound of the alkaloid group contained in Black PepperÃÂ Piper nigrumÃÂ L. The isolation method used is reflux and recrystallization methods. The reflux process in absorbing piperine compounds with diethyl ether solvent will help break down the cell walls to absorb the compounds optimally. Recrystallization was repeated 7-8 times until the crystals were pale yellow. The purity test used the TLC test with a solvent ratio of n-hexane and chloroform 6:4 with an Rf value of 0.04 cm. GCMS confirmation of 85% purity, UV-Visible spectroscopic test maximum wavelength 343 with absorbance 0.865 and FTIR test confirmed wave number 928 cm-1 (CO), 996 cm-1 ((CH bending of trans Ã¢â¬âCH=CH-), 1028 cm-1(=COC sym. st.), 1250 cm-1 (=COC asym. st.), 1440 cm-1 (methylenedioxy CH2bending), 1581 cm-1 (arom. C=C st.), 1631 cm-1 (-CO-N-). Based on the confirmed test results, the isolated compound is piperine from the alkaloid group. Piperine compounds can be used as standard compound preparations for testing the purity of compounds in research and chemistry lab work on natural ingredients.